Analisis Perhitungan Dan Perlakuan Akuntansi Bunga Simpanan Guna Menentukan PPH Final Pasal 4 Ayat 2: Studi Kasus Pada Koperasi Mantan Karyawan PT Gudang Garam Tbk. “Sekar” Jatim - Septia Mediana; Putri Awalina; Muhammad Alfa Niam (UNIVERSITAS MARITIM AMNI SEMARANG, 2024)
There are Lowest Balance, Average Balance and Daily Balance methods for calculating savings interest. The effect on PPh article 4 (2) if interest up to IDR 240,000 per month is subject to a 0% tax rate, more than IDR 240,000 per month is subject to a 10% tax rate and the effect on accounting calculations for Calculation of Business Results and Balance Sheet. The sampling technique uses the quota sampling method. Researchers determined a sample of 10 members with the criteria that members had voluntary savings of more than IDR 4,000,000. Data was obtained through interviews and documentation. From the research results, the Lowest Balance method produces interest expenses of IDR 2,003,844, Average Balance IDR 2,115,324, Daily Balance IDR 2,171,589. Of the 10 members sampled, the Lowest Balance method produces PPh article 4 (2) IDR 151,121, Average Balance IDR 151,537 and Daily Balance IDR 178,992. With details of the Lowest Balance and Average Balance methods, 6 members are subject to a PPh rate of 4 (2) 0% and 4 members are subject to a PPh rate of 4 (2) 10%. Meanwhile, for the Daily Balance method, 5 members are subject to a 0% PPh 4(2) rate, and the remaining 5 members are subject to a 10% rate. The Lowest Balance Method should be applied because it produces the smallest interest expense seen in 2021 PT Gudang Garam Tbk Former Employee Cooperative. East Java's